2020
DOI: 10.24875/ric.19003133
|View full text |Cite
|
Sign up to set email alerts
|

The Branched-chain Amino Acid Transaminase 1 -23C/G Polymorphism Confers Protection Against Acute Coronary Syndrome

Abstract: Background: Previous studies have shown an association between polymorphisms of the BAT1-NF-κB inhibitor-like-1 (NFKBIL1)-LTA genomic region and susceptibility to myocardial infarction and acute coronary syndrome (ACS). Objective: The objective of the study was to study the role of three polymorphisms in the BAT1, NFKBIL1, and LTA genes on the susceptibility or protection against ACS; we included a group of cases-controls from Central Mexico. Methods: The BAT1 rs2239527C/G, NFKBIL1 rs2071592T/A, and LTA rs1800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Recent studies have shown that the polymorphisms ( BAT1 rs2239527 C / G , NFKBIL1 rs2071592 T / A , LTA rs1800683 G / A , CASP1 rs501192 A / G , and CASP1 rs580253 A / G ) are associated with the presence of ACS, myocardial infarction, and CAD [ 5 , 6 , 7 , 8 , 15 ]. In this study, we found that the rs580253 A and rs501192 A alleles of the CASP1 gene, as well as the gene–gene interaction between BAT1 , NFKBIL1 , LTA , and CASP1 , were associated with an increased risk of developing restenosis after coronary stenting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that the polymorphisms ( BAT1 rs2239527 C / G , NFKBIL1 rs2071592 T / A , LTA rs1800683 G / A , CASP1 rs501192 A / G , and CASP1 rs580253 A / G ) are associated with the presence of ACS, myocardial infarction, and CAD [ 5 , 6 , 7 , 8 , 15 ]. In this study, we found that the rs580253 A and rs501192 A alleles of the CASP1 gene, as well as the gene–gene interaction between BAT1 , NFKBIL1 , LTA , and CASP1 , were associated with an increased risk of developing restenosis after coronary stenting.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 66 patients were placed in the restenosis group and 153 patients in the non-restenosis group. As a comparison group, we included 625 healthy individuals with neither symptoms nor previous diagnosis of cardiovascular or systemic disease previously reported [ 5 , 15 ]. All subjects were considered Mexican mestizos and ethnically matched according to ancestry informative markers (AIMs) in the ADMIXTURE software.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…BCAT has also been studied in cardiovascular diseases. BCAA aminotransferase 1-23C/G polymorphisms have been found to have a protective effect against acute coronary syndrome, but the specific mechanism has not been studied (Ramírez-Bello et al, 2020). Activation of BCAT1 and inhibition of oxoeicosanoid receptor can reduce acute myocardial infarction (Lai et al, 2021).…”
Section: Bcaas Aminotransferases and Human Diseasesmentioning
confidence: 99%